Seeing the light: depth and time restrictions in the foraging capacity of emperor penguins at Pointe Géologie, Antarctica - Rory Wilson (Aquatic Biology, 2008)
Zimmer, I., Wilson, R. P., Beaulieu, M., Nacel, A., Plötz, J. (2008). Seeing the light: depth and time restrictions in the foraging capacity of emperor penguins at Pointe Géologie, Antarctica. Aquatic Biology 3; 217-226.